The Effect of Governance on International Trade and the Mediating Role of Business Regulations - Khan, Shahedul Alam (Society & Sustainability, 2020)
The purpose of the study is to investigate the mediating role of business regulations in between the relationship of governance and international trade. Data were collected from 181 countries and the partial least squares structural equation model (PLS-SEM) was used to test the hypotheses. It was found that the business regulations practiced by a country significantly influence its international trade, but the governance of the country has a significant indirect influence on its international trade. A full mediation was evident from the results, where the indirect effect of governance on international trade was observed to be fully mediated by business regulations. The study will contribute to guiding governments and regulatory bodies to improve governance and business regulatory environment to facilitate international trade.